Effect of bergamot on lipid profile in humans: A systematic review. Issue 18 (10th October 2020) - Lamiquiz-Moneo, Itziar; Giné-González, Jaume; Alisente, Sonsoles; Bea, Ana M.; Pérez-Calahorra, Sofía; Marco-Benedí, Victoria; Baila-Rueda, Lucía; Jarauta, Estíbaliz; Cenarro, Ana; Civeira, Fernando; Mateo-Gallego, Rocío
Abstract: Dyslipidemia is a well-established modifiable cardiovascular risk. Although statins can reduce LDLc by 50–60%, less than 20% of patients with high risk of CVD achieve LDL targets. The aim of this systematic review is to evaluate the effect of the nutraceutical, bergamot ( Citrus bergamia ), on lipid parameters in humans. PubMed, Embase, Cochrane Library, and Google Scholar databases were searched for interventional and observational studies investigating the effect of bergamot on lipid profile in humans. This systematic review retrieved a total of 442 studies of which 12 articles fulfilled the eligibility criteria and were included in the qualitative synthesis. Based on data, 75% of studies showed a significant decrease in total cholesterol, triglycerides and LDLc. The decrease in total cholesterol varied from 12.3% to 31.3%, from 7.6% to 40.8% in LDLc and from 11.5% to 39.5% in triglycerides. Eight trials reported HDLc increase after intervention with bergamot. Overall, a dose-dependent and possible synergistic effect when administering with statins can be deducted from these trials. It is essential to point out that studies had heterogeneous designs and scientific quality of studies was quite limited. Promising findings reveal an alternative therapeutic option in dyslipidemia management with bergamot supplementation, especially in subjects with statins intolerance.